Tinjauan Yuridis Praperadilan Atas Penetapan Tersangka Tindak Pidana Penganiayan (Studi Putusan No.5/Pid.Pra/2021/PN.Mks) - Andi Rahmah; Asrul Aswar; Sandi Pajri (Pledoi Law Jurnal, 2024)
ABSTRACT: The district court has the authority to examine and decide, in accordance with the provisions stipulated in this law regarding whether or not an arrest, detention, termination of investigation or termination of prosecution is legal, compensation and or rehabilitation for a person whose criminal case is terminated in level of investigation or prosecution. As for what the researcher discusses, the following is the conclusion from the analysis that in the same pretrial case filed at the Makassar District Court it can be considered inappropriate in deciding the case, the decision that the researcher has reviewed is very clear that there is a value that is not fulfilled between the investigator and the judge who examines and adjudicates the case. And the author's suggestion for the government to participate in monitoring and fighting for the rights of suspects so that there is legal equality and the realization of the principle of equality before the law, for the pretrial community it can be useful to demand justice if law enforcers, in this case investigators, do not carry out their duties based on SOP and/or without seeing Party status/Agency. ABSTRAK: Pengadilan negeri berwenang untuk memeriksa dan memutus, sesuai dengan ketentuan yang diatur dalam undang-undang ini tentang Sah atau tidaknya penangkapan, penahanan, penghentian penyidikan atau penghentian penuntutan, Ganti kerugian dan atau rehabilitasi bagi seorang yang perkara pidananya dihentikan pada tingkat penyidikan atau penuntutan. Adapun yang peneliti bahas adalah sebagai berikut kesimpulan dari analisis bahwa pada Perkara Praperadilan yang sama diajukan di Pengadilan Negeri Makassar dapat dinilai kurang tepat dalam memutus perkara, putusan yang telah peneliti kaji sangat jelas bahwa ada nilai yang tidak terpenuhi antara penyidik dan Hakim yang memeriksa dan mengadili perkara tersebut. Dan saran penulis bagi pemerintah turut memantau dan memperjuangkan hak-hak tersangka sehingga terjadinya kesetaraan Hukum dan terwujudnya asas equality before the law, Bagi masyarakat praperadilan dapat bermanfaat untuk menuntut keadilan bilamana penegak Hukum dalam hal ini penyidik tidak melaksanakan tugasnya berdasarkan SOP dan/atau tanpa melihat status/Instansi Pihak Tersangka.